Adobe Photoshop CS2 : classroom in a book (Classroom in a book., 2005)
Photoshop is one of those programs that's so cool you just want to dive right in and start creating-but by plunging in head-first, without any guidance, you're likely to miss a lot. There's a solution: With this book, you learn by doing, getting your feet wet immediately as you progress through a series of hands-on projects that build on your growing Photoshop knowledge. Simple step-by-step instructions, review questions at the end of each chapter, and a companion CD with all of the book's project files make learning a breeze as the Adobe Creative Team takes you on a self-paced tour of the image-editing powerhouse. This bestselling guide has been completely revised to cover all of Photoshop CS2's new features, which include advanced tools for digital photographers, such as a new Spot Healing Brush for correcting scratches or blemishes, and Smart Sharpen for fixing photo blurring. Photoshop CS2 also includes loads of new creative tools, such as Vanishing Point and Image Warp. This comprehensive guide starts with an introductory tour of the software and then progresses on through lessons on everything from Photoshop's interface to more complex topics like color management, Web graphics, and photo retouching.